PENGARUH PENGGUNAAN INFORMASI AKUNTANSI TERHADAP PERILAKU KEUANGAN INVESTOR INDIVIDUAL UNTUK PENGAMBILAN KEPUTUSAN INVESTASI - Puspa, Loveanis Widya; Mukaram, Mukaram (Jurnal Riset Bisnis dan Investasi, 2016)
Financial behavior intended to understand the behavior of investors in making investment decisions. Decision making is a process of selecting the best alternative from a number of alternatives available under the influence of a complex situation. Investment decision will be influenced by the information received, as well as the level of ability and knowledge of investors about the investment. There is an assortment of information needed in investment to note, one of which is the accounting information. The underlying concept is that the accounting information for the stock value of a company is influenced by the financial performance of the company concerned. Accounting information used by capital market investors are Statements of Financial Position, Statement of Comprehensive Income, Statement of Changes in Equity and Cash Flow Statement. This study aims to determine the effect of the use of accounting information to the financial behavior of individual investors in making investment decisions. The survey was conducted on 110 investor PT Phillips Securities Indonesia Bandung branch. Primary data was collected through questionnaire distribution and it is analyzed descriptively. This study resulted in the average number for the use of accounting information of 3.85 which means that the accounting information has been used well by investors. The average values for financial behavior is of 3.52, it can be interpreted that the financial behavior of investors in making investment decisions is good. For R Square obtained by 0.6%, proving that the accounting information contributed for 0.6% of the financial behavior of investors. As for the P value of 0.406, The figure is greater than 0.05, which is shows us that obtained figures which show that the use of accounting information has no influence on the financial behavior of individual investors for making investment decisions. So, although the results of this study indicate that the effect of accounting information on the behavior of financial investors when deciding on an investment is not significant, but investors stated that the accounting information presented by the company remain a consideration in the investment decision-making process.